PENGGUNAAN AUKSIN ALAMI SEBAGAI ZAT PENGATUR TUMBUH (ZPT) TERHADAPPERTUMBUHAN STEK BIBIT JAMBU AIR (Syszygium samarangense) - Bonefasius Dule; Murdaningsih Murdaningsih (Agriculture Faculty of Flores University, 2017)
Use of Natural Auksin as Growth Zat (ZPT) Against Growth of Stam Breeding Water Jamboo (Syszygium samarangense).This study aims to determine the effect of the use of auksin extract of onion, garlic extract and onion extract as well as the effect of the best extract on the growth of water cashew cuttings (Syzygium samarangense)The study was arranged by Randomized Block Design with single factor pattern consisting of four treatments ie without auxin (A-0), auksin extract of onion (A-1), auksin garlic extract (A-2) and auksin garlic extract bombai (A-3). The observation variables in this study were: percentage of live cuttings (%), root length (cm), root quantity, fresh root weight (g), fresh weight weight (g), dry root weight (g) and dry weight weight (g)The results showed the use of axin onion extract 90%, can increase the percentage of live cuttings (2.99%), root length (51.22%); number of roots (56.55%), fresh root weight (47.54%); weight of fresh stover (26.22%); dry root weight (51.72%) and weight of dry stover (27.64%). The use of 90% onion extract gave the best influence to the growth of root cashew cuttings which resulted in live cuttings percentage (98.86%); root length (10.04 cm); number of roots (19,20); fresh root weight (2.02 g); fresh fresh weight (17.22 g); dry weight of roots (1.06 g) and weight of dry stover (8.60 g).